Analysis of the gut-specific microbiome from field-captured tsetse flies, and its potential relevance to host trypanosome vector competence - Griffith, Bridget C.; Weiss, Brian L.; Aksoy, Emre; Mireji, Paul O.; Auma, Joana E.; Wamwiri, Florence N.; Echodu, Richard; Murilla, Grace; Aksoy, Serap (BMC microbiology, 2018)
The tsetse fly (Glossina sp.) midgut is colonized by maternally transmitted and environmentally acquired bacteria. Additionally, the midgut serves as a niche in which pathogenic African trypanosomes reside within infected flies. Tsetse’s bacterial microbiota impacts many aspects of the fly’s physiology. However, little is known about the structure of tsetse’s midgut-associated bacterial communities as they relate to geographically distinct fly habitats in east Africa and their contributions to parasite infection outcomes. We utilized culture dependent and independent methods to characterize the taxonomic structure and density of bacterial communities that reside within the midgut of tsetse flies collected at geographically distinct locations in Kenya and Uganda. Results: Using culture dependent methods, we isolated 34 strains of bacteria from four different tsetse species (G. pallidipes, G. brevipalpis, G. fuscipes and G. fuscipleuris) captured at three distinct locations in Kenya. To increase the depth of this study, we deep sequenced midguts from individual uninfected and trypanosome infected G. pallidipes captured at two distinct locations in Kenya and one in Uganda. We found that tsetse’s obligate endosymbiont, Wigglesworthia, was the most abundant bacterium present in the midgut of G. pallidipes, and the density of this bacterium remained largely consistent regardless of whether or not its tsetse host was infected with trypanosomes. These fly populations also housed the commensal symbiont Sodalis, which was found at significantly higher densities in trypanosome infected compared to uninfected flies. Finally, midguts of field-captured G. pallidipes were colonized with distinct, low density communities of environmentally acquired microbes that differed in taxonomic structure depending on parasite infection status and the geographic location from which the flies were collected. Conclusions: The results of this study will enhance our understanding of the tripartite relationship between tsetse, its microbiota and trypanosome vector competence. This information may be useful for developing novel disease control strategies or enhancing the efficacy of those already in use.
Keywords: Tsetse fly; Glossina; Symbiont; Wigglesworthia; Sodalis; Microbiota; African trypanosome; Metagenomics